Early Clinical Experiences for Second-Year Student Pharmacists at an Academic Medical Center - McLaughlin, Jacqueline E. (Am J Pharm Educ, 2015)
Objective. To examine student outcomes associated with the Student Medication and Reconciliation Team (SMART) program, which was designed to provide second-year student pharmacists at the University of North Carolina (UNC) Eshelman School of Pharmacy direct patient care experience at UNC Medical Center. Design. Twenty-two second-year student pharmacists were randomly selected from volunteers, given program training, and scheduled for three 5-hour evening shifts in 2013-2014. Pre/post surveys and reflection statements were collected from 19 students. Data were analyzed with a mixed methods approach. Assessment. Survey results revealed an increase in student self-efficacy (p<0.05) and positive perceptions of SMART. Qualitative findings suggest the program provided opportunities for students to develop strategies for practice, promoted an appreciation for the various roles pharmacists play in health care, and fostered an appreciation for the complexity of real-world practice. Conclusion. Early clinical experiences can enhance student learning and development while fostering an appreciation for pharmacy practice.